1968
DOI: 10.1139/f68-207
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Aggression and in Strength of the Social Hierarchy among Juvenile Atlantic Salmon Deprived of Food

Abstract: Aggressive behaviour of Atlantic salmon (Salmo salar) parr, tested in groups of eight, was greater during 3 days of deprivation of food than during 3 days of feeding. Frontal and lateral displaying appeared to increase more than charging and nipping. I.rcreased agression was only partly a result of increased locomotion, and therefore was partly a direct effect of hunger.Strong social hierarchies developed, larger fish nipping smaller ones more than the reverse. The correlation between size and hierarchical sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
2
3

Year Published

1970
1970
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(79 citation statements)
references
References 0 publications
4
70
2
3
Order By: Relevance
“…The low aggression between the size-classes indicates that these fish do not show severe competition. Greatest social conflict usually occurs between fish of similar size (Newman 1956;Symons 1968), and small differences in size can determine dominance (Chapman 1962). However, with increasing size disparity fish require different foods, hence behaviour which focuses competition on fish of similar size would be adaptive (Symons 1968).…”
Section: Discussionmentioning
confidence: 99%
“…The low aggression between the size-classes indicates that these fish do not show severe competition. Greatest social conflict usually occurs between fish of similar size (Newman 1956;Symons 1968), and small differences in size can determine dominance (Chapman 1962). However, with increasing size disparity fish require different foods, hence behaviour which focuses competition on fish of similar size would be adaptive (Symons 1968).…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of using feeding behaviour to assign dominance is that it enables the assessment of social hierarchies in larger groups of fish than is possible using the standard approach of observing aggressive interactions between individuals. The distribution of food between individuals within a group and the strength of the social hierarchy will be dependent on the availability of food (Symons, 1968;McCarthy et al 1992;Olla et al 1992). This is demonstrated in Fig.…”
Section: Ian D Mccarthy and Others Feeding Behaviourmentioning
confidence: 99%
“…Although the fish in both groups were of a similar size and under the same feeding regimen, both the range of meal sizes and the range of individual values for CV, were significantly different for the two groups indicating that the strength of the social hierarchy, inferred from the correlation coefficient, varied between the two groups. Previous studies have shown that the strength of the social hierarchy can vary between groups of fish given the same treatment (Symons, 1968;Winberg et al 1992Winberg et al , 1993. Under these conditions, it appears that the strength of the social hierarchy is dependent on the particular individuals present in the group and the differences in competitive ability and aggression between individuals in each group.…”
Section: Ian D Mccarthy and Others Feeding Behaviourmentioning
confidence: 99%
“…For instance, SHELBOURNE (1964) reported that smaller fish were more prone to pigment deficiency, but RIL~X & THACK~V, (1963) found no effect of size. Aggressive behaviour of young salmon, Salrno salar (SYMoNS 1968) in the form of frontal and lateral displaying as well as in charging and nipping was more prevalent during lack of food. Strong hierachies based on size then developed.…”
Section: Undesirable Input In Fishmentioning
confidence: 95%